On the Anion Exchange of PX3 (X = Cl, Br, I) in Ionic Liquids comprising Halide Anions. Issue 1 (16th December 2016) - Wolff, Alexander; Pallmann, Julia; Brunner, Eike; Doert, Thomas; Ruck, Michael
Abstract : Mixtures of the phosphorus(III) halides P X 3 ( X = Cl, Br, I) and the ionic liquids [HMIm][ X ] ( X = Cl, Br, I; HMIm = 1‐hexyl‐3‐methylimidazolium) were studied by nuclear magnetic resonance and Raman spectroscopy. The chloride PCl3 was found to be stable in all mixtures, whereas PBr3 and PI3 can undergo halide exchange depending on the anion of the utilized ionic liquid. The exchange occurs immediately after mixing the compounds at room temperature. In contrast to previous observations made in conventional solvents, intermediate mixed phosphorus halides have not been observed in ionic liquids, indicating a rapid exchange under the applied conditions. Compared to the chemical shifts observed in nuclear magnetic resonance spectra of pure P X 3 liquids, the signal of PCl3 is strongly shifted upfield in [HMIm][Cl] indicating strong interaction between the phosphorus halide and the surrounding ionic liquid. Abstract :